Optimization of Dispersive Liquid-Liquid Microextraction Based on Solidification of Floating Organic Drop of Endocrine Disrupting Compounds in Liquid Food Samples Using Response Surface Plot Method - Li, Yu; Zhang, Chen (Asian Journal of Chemistry, 2014)
A dispersive liquid-liquid microextraction-solidification of floating organic drop (DLLME-SFO) method was developed for the endocrine disrupting compounds (estrone, estradiol, estriol, bisphenol A, diethylstilbestrol and 4-nonylphenol) extraction in food samples. The samples were analyzed by high-performance liquid chromatography with UV detection. Meanwhile, the conditions of endocrine disrupting compounds extraction were optimized by a response surface plot method. The result indicated that the optimum conditions for endocrine disrupting compounds extraction were: 100 μL dodecanol, 0.6 mL acetonitrile, 5 mL sample and 0.5 g NaCl. The linear range of the method was 0.01-3 mg/L and the limits of detection were 0.41-7.50 μg/L. In addition, spiking experiments were performed in soy milk, cow's milk and drinking water and the relative recoveries of the endocrine disrupting compounds ranged from 71.34-112.97 % with RSDs in the range of 0.11-11.18 %. The experimental results indicated that the method was suitable to apply in food samples.